Strengthening The Village Economy Through Educational Tourism: Village Owned Enterprise Role Managing Manahayu Holistic Farm In Batu City: Penguatan Ekonomi Desa Melalui Eduwisata: Peran Badan Usaha Milik Desa Dalam Pengelolaan Manahayu Holistic Farm di Kota Batu - Daffa Justice Privian; Prisca Kiki Wulandari (Universitas Indo Global Mandiri, 2026)
Purpose : This study analyzes the role of the Village-Owned Enterprise (BUMDes) in managing the Manahayu Holistic Farm educational tourism program, which is based on local agricultural potential, in Giripurno Village, Bumiaji District, Batu City. Design/methodology/approach : This study employs a qualitative approach using a case study design. Data collection was conducted through in-depth interviews, observations, and documentation with informants selected via purposive sampling, including the village head, village secretary, director of the village-owned enterprise (BUMDes), employees, and villagers. Data analysis utilized the interactive model proposed by Miles, Huberman, and Saldana. Findings : The research findings indicate that the management of Manahayu educational tourism exhibits asymmetrical management practices. Practical Implication : Strengthening human resource capacity, institutionalizing community participation, and developing standard operating procedures for oversight are urgent priorities for ensuring the sustainability of educational tourism based on local potential. Originality/value : This study provides a new perspective by systematically identifiying th strengths and weaknesses of each management function, offering a comprehensive understanding of educational tourism management.